2010
DOI: 10.1227/neu.0b013e3181ef25c5
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Transsphenoidal Pituitary Surgery: Evidence of an Operative Learning Curve

Abstract: The improvements in the duration of surgery and visual outcome noted after about 50 endoscopic procedures would favor the existence of an operative learning curve for these parameters. This further highlights the benefits of subspecialization in pituitary surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
104
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(118 citation statements)
references
References 36 publications
7
104
0
7
Order By: Relevance
“…8, 25 The current literature focuses on 2 major techniques for the endoscopic transnasal approach to the sella, with or without use of a speculum. With help of a nasal speculum, which is used to dilate the working channel, the neurosurgeon reaches the sphenoid sinus through 1 nostril, the mononostril or monoportal approach.…”
Section: Discussionmentioning
confidence: 99%
“…8, 25 The current literature focuses on 2 major techniques for the endoscopic transnasal approach to the sella, with or without use of a speculum. With help of a nasal speculum, which is used to dilate the working channel, the neurosurgeon reaches the sphenoid sinus through 1 nostril, the mononostril or monoportal approach.…”
Section: Discussionmentioning
confidence: 99%
“…Sonnenburg et al evaluated their results with pi- 30 Another study demonstrated significant improvement in visual outcome and operating time after 50 endoscopic endonasal pituitary cases. 18 It would seem self-evident that there would be a learning curve in expanded endonasal cranial base procedures in which the depth of surgical field is increased and the lesions are more intimately associated with critical neurovascular structures. 31,32 However, there is a paucity of evidence to demonstrate this learning curve and provide appropriate recommendations.…”
Section: Learning Curve In Craniopharyngioma Surgerymentioning
confidence: 99%
“…In fact, very little published documentation exists regarding the learning curve associated with endonasal cranial base cases in general. 17,18,24,30,33 The purpose of the present study was to determine if, and to what extent, a learning curve exists for the endoscopic transnasal resection of craniopharyngiomas.…”
mentioning
confidence: 99%
“…15 Specifically, nasal preparation was performed with topical application of preoperative decongestants (cophenylcaine, Aurum Ltd.) into both nostrils. No antiseptic wash or injection of vasoconstrictors was used.…”
Section: Operative Techniquementioning
confidence: 99%